MANAJEMEN PEMBELAJARAN PARTISIPATIF BERBASIS PROJECT BASED LEARNING PADA MATERI FISIKA HUKUM PASCAL - Santria Umar; Patricia Mardiana Silangen; Theresje Mandang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to provide a clear and comprehensive picture to students of class XI IPA 2 SMA Negeri 3 Tondano about learning management which includes planning, organizing, implementing, and evaluating participatory learning based on project-based learning on pascal’s law material in physics subjects. The method used in this research is mix method with concurrent model which is a combination of two methods, especially qualitative and quantitative. The structure of this research uses qualitative methods while quantitative methods are used to assist qualitative information. The results of this study are starting from the planning stage including the syllabus and lesson plans adapted to the strategy. The next stage is organizing which result in the function and role of management components. The implementation stage is in accordance with the syntax of participatory learning. This implementation stage shows that the implementation of management functions in participatory learning based on project-based learning on pascal’s law physics material for SMA N 3 Tondano class XI IPA 2 students can shape students’ cognitive, affective and psychomotor competencies through making learning projects. Based on the results of the study, it is concluded that planning, organizing, implementing and evaluating participatory learning based on project-based learning is well implemented as seen from the cognitive, affective and psychomotor assessment rubrics.